Philosophy and right: Sartrean freedom in the right of this century - VILLALOBOS ANTÚNEZ, JOSÉ V.; DÍAZ ZULUAGA, LUIS E.; DÍAZ-CID, LUIS (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Sartre outlines and draws its philosophical ideas which have effects in the post-modern man (FLAJOLIET, Alain. (2009). This research aims to understand the incidence of the philosophical thought of the freedom from Sartre, in the Law of the New Age. The textual and literary criticism, philosophical hermeneutics were used; methods of philology and Linguistics as well; but above all, the eclectic method. The human freedom is the ability of consciousness to transcend its material situation. Human beings are free only if their basic needs, in practice, they are met. The Freedom implies that human beings are free in all situations.